Strategy and the management of libraries of the Hungarian nationality in Slovenia - Zágorec-Csuka, Judit (Anali PAZU, 2022)
The author addresses the strategy and the management of libraries in the Hungarian bi-lingual areas in Slovenia, where different nationalities reside in Pomurje and the European Union, and offers new ways for the libraries to enable the Hungarian minority to participate in the `intelligent region´ of the information society, as a society of knowledge and innovations. It all leads to the domination of digital librarianship.